Peran Penentuan Tipe Kapal dan Kargo dalam Memediasi Pengaruh Kepemimpinan dan Komitmen Organisasi terhadap Kinerja Bongkar Muat: Studi Empiris di Perusahaan Pelayaran Wilayah Banten - Dana Rizky Kurniawan; Tata Rustandi; Udin Suadma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to examine and analyze the role of determining the type of ship and cargo in mediating the influence of leadership and organizational commitment on loading and unloading performance. This study uses primary data obtained from the results of distributing questionnaires via google form to 106 operators at Banten Port. Data is processed using SmartPLS 3.2.9. The results of the study indicate that leadership has a positive and significant effect on loading and unloading performance, organizational commitment has a positive and significant effect on loading and unloading performance, leadership has a positive and significant effect on ship and cargo type, organizational commitment has a positive and significant effect on ship and cargo type, ship and cargo type has a positive and significant effect on loading and unloading performance, ship and cargo type is able to mediate positively and significantly the influence of leadership on loading and unloading performance, ship and cargo type is able to mediate positively and significantly the influence of organizational commitment on loading and unloading performance.